Population status and distribution of Hinde’s Babbler (Turdoides hindei) in Meru national park and Ngaya Forest Reserve areas of Meru county, Kenya - Onyancha, Fredrick; Eshiamwata, George; Karanja, Henry; Njoroge, Peter (International Journal of Biological Research, 2016)
Hinde’s Babbler which is listed as Vulnerable in the IUCN Red List with isolated populations confined to some parts of central and eastern Kenya. A survey was conducted between June and December, 2015 to assess and compare population status of Hinde’s Babbler across a gradient of levels of protection. Data was collected at intervals of 100m along predetermined cumulative 19 km transects where playback of Hinde’s Babbler was used to elicit response of individual groups. At each point of detection, total number of adults, offsprings and vegetation phenology was recorded. The entire habitat population was 540 individuals (dry season; Ngaya FR-255, Meru NP-137 and Agricultural landscape- 148), 411 individuals (wet season; Ngaya FR-168, Meru NP-185 and Agricultural landscape- 58) though there was no significant statistical difference between the seasonal datasets. There was significance difference between adults and juveniles in both seasons (Mann Whitney, Dry P= 0.0001 and wet season, P = 0.0002). These results imply that the three sites are vital for the survival, conservation and management of this threatened species and hence continuous monitoring of protected and unprotected sites is necessary for conservation of threatened avian species like Hinde’s Babbler.